2011
DOI: 10.1111/j.1744-7348.2011.00521.x
|View full text |Cite
|
Sign up to set email alerts
|

Farmland bird invertebrate food provision in arable crops

Abstract: Invertebrates are an essential food source for most farmland birds yet their relative abundance and biomass in the most commonly grown arable crops are poorly understood. Dvac suction sampling was used to determine the abundance, biomass and community composition of those invertebrate groups considered important in the diet of farmland birds for the commonest arable crops. Approximately 40 fields were sampled at the edge and mid‐field over 2 years in three different locations in England. In cereals, the fauna … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 50 publications
0
28
0
3
Order By: Relevance
“…This is a result we would expect if resource separation resulting from farming specialization was important for population regulation. Farms in landscapes with mainly intensive crop farming may sustain sufficient seed availability during winter for House Sparrows that often forage in seed storage facilities, but provide relatively few insects important for chick rearing during breeding and thereby limit populations (Brickle et al 2000, Holland et al 2012. However, populations in mixed landscapes, with mainly animal husbandry, may have sufficient food supply during breeding (Moller 2001) but suffer from limiting mechanisms acting during the winter.…”
Section: Discussionmentioning
confidence: 99%
“…This is a result we would expect if resource separation resulting from farming specialization was important for population regulation. Farms in landscapes with mainly intensive crop farming may sustain sufficient seed availability during winter for House Sparrows that often forage in seed storage facilities, but provide relatively few insects important for chick rearing during breeding and thereby limit populations (Brickle et al 2000, Holland et al 2012. However, populations in mixed landscapes, with mainly animal husbandry, may have sufficient food supply during breeding (Moller 2001) but suffer from limiting mechanisms acting during the winter.…”
Section: Discussionmentioning
confidence: 99%
“…We used a nominal categorization of species' specialization to farmland habitats (Farm, http://www.ebcc.info/wpimages/other/SpeciesClassification2012.xls) and scored species for their main breeding and winter diet type using categories of insectivores ( I ), herbivores ( H ), and species with a mixed or omnivorous diet ( O ). The assignment was based on multiple published data sets (Bohning‐Gaese & Oberrath, ; Gregory et al ., ; Van Turnhout et al ., ; Holland et al ., ) and a review of the standard literature (Cramp et al ., ). Finally, log‐transformed average body length (logBody) was obtained from (Cramp et al ., ).…”
Section: Methodsmentioning
confidence: 99%
“…As could be expected, higher total numbers of invertebrates were to be found at the field edges than the mid-field. Strikingly, Holland et al (2012) demonstrated that, in all 40 common crop fields investigated in their study, the chick-food index was only half or less the level required to ensure sufficient chick survival for the maintenance of the population of the grey partridge. Frampton and Dorne (2007) quantified the impact of reduced PPP input on the abundance of several arthropod groups, including so-called 'chick-food insects'.…”
Section: Non-target Arthropods As Food Web Supportmentioning
confidence: 99%
“…Next to the results of the investigations above, showing a strong decrease of NTAs as food web support in fields treated with PPPs, Holland et al (2012) investigated the NTA diversity and calculated the chick-food index in 40 agricultural fields, cultivated with cereals, oil seed rape, peas, beans or potatoes. As could be expected, higher total numbers of invertebrates were to be found at the field edges than the mid-field.…”
Section: Non-target Arthropods As Food Web Supportmentioning
confidence: 99%